Using the Delphi Method to Establish Expert Consensus A Practical Guide - Jorm, Anthony; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2025)
This Open Access book provides detailed practical guidance on how to do a Delphi study to establish a consensus across the broad range of social, psychological, health and environmental sciences. The book informs the design of Delphi studies by drawing on wisdom-of-crowds research on the conditions under which groups make better-quality judgements. It covers the development of the Delphi method and its many variations, as well as the ways this method has been used to make judgements of facts where the evidence is imperfect, set methodological standards, make predictions, define foundational concepts, determine collective values, and improve professional practice and policy. It takes the reader through the steps in carrying out a Delphi study and the choices that have to be made at each step. It also covers the implementation of Delphi findings in practice. Case examples are included throughout drawing from a variety of disciplines. Anthony Jorm is an Emeritus Professor at the University of Melbourne and National Health & Medical Research Council Leadership Fellow, Australia. His research focuses on building the community$1 (Bs capacity for prevention and early intervention with mental disorders. He has been an author of over 60 studies using the Delphi method.s
Chapter 1: Origins and Uses of the Delphi Method -- Chapter 2: Comparison of Delphi with Other Consensus Methods -- Chapter 3: Conditions for a Valid Consensus -- chapter 4: Steps in Carrying out a Delphi Study -- Chapter 5: Implementing the Findings of Delphi Studies in Practice.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sociology -- Methodology; Psychology -- Methodology; Technology -- Sociological aspects; Medical policy; Environmental policy; Environmental sciences -- Social aspects; Sociological Methods; Psychological Methods; Science, Technology and Society; Health Policy; Environmental Policy; Environmental Social Sciences